Abbiamo veramente bisogno dell’identità? Alcune precauzioni per l’uso di un concetto ambiguo - Caniglia, Enrico (SocietàMutamentoPolitica, 2013)
The essay critically discusses some theoretical and empirical aporias that characterize the sociological concept of identity. In particular, it highlights the common sense origin of the category of identity and the characteristics of essentialism and realism that characterize its psychological root. Finally, it puts forward an alternative way of research according to which the identity no longer identifies a real group but a discursive practice.